Pyrethroid tolerance is associated with elevated expression of antioxidants and agricultural practice in Anopheles arabiensis sampled from an area of cotton fields in Northern Cameroon - PIE MÜLLER; MOUHAMADOU CHOUAÏBOU; PATRICIA PIGNATELLI; JOSIANE ETANG; EDWARD D. WALKER; MARTIN J. DONNELLY; FRÉDÉRIC SIMARD; HILARY RANSON (Molecular Ecology, 2008)
Spraying of agricultural crops with insecticides can select for resistance in nontarget insects and this may compromise the use of insecticides for the control of vector‐borne diseases. The tolerance of the malaria vector, Anopheles arabiensis to deltamethrin was determined in a field population from a cotton‐growing region of Northern Cameroon both prior to and midway through the 4‐month period of insecticide application to the cotton crop. A 1.6‐fold increase in the median knockdown time was observed. To determine whether this increased tolerance was associated with constitutively elevated levels of genes commonly associated with insecticide resistance, RNA was extracted from F 1 progeny from family lines of field‐caught mosquitoes and hybridized to the Anopheles gambiae detox chip. The experimental design avoided the confounding effects of colonization, and this study is the first to measure gene expression in the progeny of gravid, wild‐caught mosquitoes. Several genes with antioxidant roles, including superoxide dismutases, a glutathione S‐transferase and a thioredoxin‐dependent peroxidase, and a cytochrome P450 showed elevated expression in mosquito families collected during the insecticide‐spraying programme. These genes may constitute an important general defence mechanism against insecticides. Intriguingly, the levels of expression of these genes were strongly correlated suggesting a common regulatory mechanism.